Associations of depressive symptoms and history with three a priori diet quality indices in middle-aged and older adults - Elstgeest, Liset E.M.; Winkens, Laura H.H.; Penninx, Brenda W.J.H.; Brouwer, Ingeborg A.; Visser, Marjolein (Journal of affective disorders, 2019)
•Current depressive symptoms were associated with lower MDS and AHEI scores in men.•Chronic depressive symptoms were associated with lower MDS and AHEI scores.•No associations were found for emerging and remitted depressive symptoms with diet.•A history of depressive symptoms was related to lower MDS and AHEI scores in men.•No consistent associations were found with depressive symptoms and the DASH score. Evidence for the diet-depression link is growing but longitudinal studies on the reverse association are scarce. We investigated associations of (1) current depressive symptoms, (2) short-term changes in and (3) long-term history of depressive symptoms with three a priori diet quality indices. Data were from participants (≥ 55 years) of the Longitudinal Aging Study Amsterdam (LASA). The Mediterranean Diet Score (MDS), Alternative Healthy Eating Index (AHEI-2010) and Dietary Approaches to Stop Hypertension diet (DASH) were derived in 2014/2015. Depressive symptoms (Center for Epidemiologic Studies Depression scale; CES-D) were assessed in 2014/2015 and at five regular 3-yearly cycles from 2001–2003 to 2015/2016. Associations between three depression determinants and the diet indices were analysed by multivariable linear regression models. Cross-sectionally (n = 1312), current depressive symptoms (CES-D ≥ 16) were associated with lower MDS (adjusted B = −1.21, 95%CI = −2.41, −0.023) and AHEI (B = −2.72, 95%CI = −5.24, −0.20) scores in men only. Chronic/recurrent depressive symptoms (CES-D ≥ 16 in both 2011–2013 and 2015/2016) were associated with lower MDS scores (n = 1233; B = −2.22, 95%CI = −3.40, −1.04) and a trend for lower AHEI scores (B = −2.37, 95%CI = −4.92, 0.18), compared to no depressive symptoms (twice CES-D < 16). History of depressive symptoms (ever CES-D ≥ 16 from 2001–2003 to 2011–2013; n = 687) was associated with lower MDS (B = −1.87, 95%CI = −3.47, −0.27) and AHEI (B = −4.33, 95%CI = −7.54, −1.13) scores in men only. No associations were found with the DASH score. Single dietary data collection impeded investigation of prospective depression-diet associations. Our study in middle-aged and older adults suggests that current and past depressive symptoms are associated with poorer diet quality, particularly in men.